2021
DOI: 10.1155/2021/9941538
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antidiabetic Medications among Women with Gestational Diabetes

Abstract: Background. Optimal adherence to prescribed medications in women with gestational diabetes is relevant for perinatal outcomes. Objective. To summarize available information on the prevalence and factors contributing to medication adherence in women with gestational diabetes from the biological and psychosocial perspectives. Methods. A literature search on adherence in gestational diabetes was conducted in PubMed/MEDLINE, CINAHL, Scopus, and the Directory of Open Access Journals for studies published on the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Moreover, according to the report of a systematic review and meta-analysis conducted in Ghana, it is indicated that antidiabetic medication non-adherence stands between 35.6%-97%. Comparing these findings to the present study, it could be noticed that the prevalence of 45.5% non-compliance to antidiabetic medication falls within what is established by the systematic review report and as such correlates well with this study report [31].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, according to the report of a systematic review and meta-analysis conducted in Ghana, it is indicated that antidiabetic medication non-adherence stands between 35.6%-97%. Comparing these findings to the present study, it could be noticed that the prevalence of 45.5% non-compliance to antidiabetic medication falls within what is established by the systematic review report and as such correlates well with this study report [31].…”
Section: Discussionsupporting
confidence: 92%